(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The study purpose is to determine the optimal distance between black haloxylon neighboring plants. The black haloxylon plants influence at different distances on aboveground phytomass annual growth of wormwood-ephemeral vegetation was studied by laying transects between neighboring individuals. With a very close location of its individuals (the distance between individuals is 3.6 m), the wormwood-ephemeral vegetation productivity decreases sharply, and with a significant distance from each other (the distance between individuals is 6.3-8.1 m) it sharply decreases. It has been established that under the Karnabchul conditions, this edificator species individual’s optimal placement relative to each other is 4.5-5.4 m (on average 4.85 m). With this black haloxylon plants arrangement, their negative influence is significantly reduced, which leads to an increase in wormwoodephemeral vegetation productivity.